CaMKII at the crossroads: calcium dysregulation, and post‐translational modifications driving cell death - Mattiazzi, Ramona Alicia (2025)
The multifunctional Ca2+/calmodulin-dependent protein kinase II (CaMKII) regulates numerous proteins involved in excitation–contraction–relaxation coupling and cardiac excitability. However, its overactivation induces severe Ca2+/handling alterations, playing a significant role in the pathogenesis of diseases such as hypertrophy, arrhythmias and cell death, which can ultimately lead to heart failure. Being a suitable target for various aberrant signals that characterize several diseases, such as Ca2+ overload, oxidative stress or excessive glycosylation, CaMKII shifts under these conditions from a physiological regulator to a pathological molecule. In this review, we explore the evolution of knowledge regarding the role of CaMKII activation on cell death across different pathological contexts, focusing on the converging mechanisms that transform the enzyme from an ally into a villain.